Game changer—talent transfer pathways in sport: a systematic review - Green, A.; Fleischman, D.; Mulcahy, R.; Kean, B. (Frontiers in Sports and Active Living, 2024)
Research question Talent transfer, an accelerated sport pathway to expertise, holds considerable appeal for sports organisations. As an emerging area of academic research across a range of sport disciplines, there is opportunity for to advance knowledge and practice. This review aimed to (a) explore how talent transfer has been defined, to develop a synthesised definition; (b) systematically identify the factors that influence talent transfer; and (c) investigate how theory underpins and enhances understanding of talent transfer.